Detection of chlorobenzene in water using a wettability-controlled three-dimensional graphene selective filter. (2nd December 2016) - Lim, Taekyung; Lee, Jaejun; Kim, Jihyoung; Seo, Sungwon; Ju, Sanghyun
Abstract: An oxide nanowire transistor covered with a wettability-controlled three-dimensional (3D) graphene filter was fabricated to detect chlorobenzene in water. The 3D porous graphene filter allowed chlorobenzene to pass through while blocking water because of its wettability. The chlorobenzene concentration in water could be monitored by observing the threshold voltage shift, which moved to the negative direction with increasing chlorobenzene concentration in water. The advantage of the fabricated device is that it can be used to easily estimate the chlorobenzene concentration in water by consistently monitoring current.